Thinking Outside the Box: Innate- and B Cell-Memory Responses as Novel Protective Mechanisms Against Tuberculosis - Choreño-Parra, José Alberto; Weinstein, León Islas; Yunis, Edmond J.; Zúñiga, Joaquín; Hernández-Pando, Rogelio (Frontiers in Immunology, 2020)
Tuberculosis (TB) is currently the deadliest infectious disease worldwide. Failure to create a highly effective vaccine has limited the control of the TB epidemic. Historically, the vaccine field has relied on the paradigm that IFN-γ-mediated CD4+ T cell memory responses are the principal correlate of protection in TB. Nonetheless, the demonstration that other cellular subsets offer protective memory responses against Mycobacterium tuberculosis (Mtb) is emerging. Among these are memory-like features of macrophages, myeloid cell precursors, natural killer (NK) cells, and innate lymphoid cells (ILCs). Additionally, the dynamics of B cell memory responses have been recently characterized at different stages of the clinical spectrum of Mtb infection, suggesting a role for B cells in human TB. A better understanding of the immune mechanisms underlying such responses is crucial to better comprehend protective immunity in TB. Furthermore, targeting immune compartments other than CD4+ T cells in TB vaccine strategies may benefit a significant proportion of patients co-infected with Mtb and the human immunodeficiency virus (HIV). Here, we summarize the memory responses of innate immune cells and B cells against Mtb and propose them as novel correlates of protection that could be harnessed in future vaccine development programs.